The effect of percutaneouS vs. cutdoWn accEss in patients after Endovascular aorTic repair (SWEET): Study protocol for a single-blind, single-center, randomized controlled trial - Zhou, Yuhang; Wang, Jiarong; Zhao, Jichun; Yuan, Ding; Weng, Chengxin; Wang, Tiehao; Huang, Bin (Frontiers in Cardiovascular Medicine, 2022)
Background: Endovascular aortic repair (EVAR) and Thoracic endovascular aortic repair (TEVAR) have become the first-line treatment for aortic diseases, but current evidence is uncertain regarding whether a percutaneous approach has better outcomes than cutdown access, especially for patient-centered outcomes (PCOs). This study is designed to compare these outcomes of percutaneous access versus cutdown access after endovascular aortic repair. Method: The SWEET study is a randomized, controlled, single-blind, single-center non-inferiority trial with two parallel groups in two cohorts respectively. After eligibility screening, subjects who meet the inclusion criteria will be divided into Cohort EVAR or Cohort TEVAR according to clinic interviews. And then participants in two cohorts will be separately randomly allocated to either intervention groups receiving percutaneous access endovascular repair or controlled groups receiving cutdown access endovascular repair. Primary clinician-reported outcome (ClinRO) is access-related complication, and primary patient-centered outcome (PCO) is time back to normal life. Follow-up will be conducted at two weeks, one month, three months postoperatively. Discussion: The choice of either percutaneous or cutdown access may not greatly affect the success of EVAR or TEVAR procedures, but can influence the quality of life and patient-centered experience. Given the very low evidence for ClinROs and few data for PCOs, comparison of the percutaneous versus cutdown access EVAR and TEVAR is essential for both patient-centered care and clinical decision making in endovascular aortic repair. Trial registration: Chinese Clinical Trial Registry ChiCTR2100053161 (registered on 13th November, 2021).